Sabrina Fludde - Fisk, Pauline (London : Bloomsbury, 2005)
A girl who has lost her memory makes new friends in an English town and finds her own way of discovering who she is.
6.2
5-8.
5-8
Keywords: Amnesia -- Fiction; Identity -- Fiction; Amnesia -- Fiction; Identity (Psychology) -- Fiction; England -- Fiction; England -- Fiction